2005
DOI: 10.1164/rccm.200507-1072oc
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Moxifloxacin and Rifapentine Is More Active Than the Denver Regimen in Murine Tuberculosis

Abstract: Rationale: Treatment of tuberculosis with an efficacious once-weekly regimen would be a significant achievement in improving patient adherence. Currently, the only recommended once-weekly continuation phase regimen of isoniazid plus rifapentine (10 mg/kg) is inferior to standard twice-weekly therapy with isoniazid plus rifampin and is, therefore, restricted to non-high-risk patients. The substitution of moxifloxacin, a new 8-methoxyfluoroquinolone, for isoniazid and an increase in the dose of rifapentine could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
60
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 23 publications
4
60
0
Order By: Relevance
“…Recent experience in the murine model of TB supports the latter observations. Daily administration of the 6-mo RHZ-based regimen is significantly more effective than the same regimen administered according to a predominantly twice-weekly schedule (9).…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Recent experience in the murine model of TB supports the latter observations. Daily administration of the 6-mo RHZ-based regimen is significantly more effective than the same regimen administered according to a predominantly twice-weekly schedule (9).…”
mentioning
confidence: 89%
“…This led us to hypothesize that using P twice weekly rather than once weekly would significantly increase the rifamycin exposure and result in activity similar to that of standard daily therapy. Prior experience in the murine model suggested that the substitution of moxifloxacin (M) for H would lead to additional gains in activity (9,20,21).In the current series of studies, the bactericidal and sterilizing activities of modified twice-weekly regimens were compared with those of standard daily therapy in the murine model of TB. In Study 1, we used the predominantly twice-weekly RHZ-based regimen as the foundation to assess the effect of three modifications: substitution of M for H, substitution of P for R during the intermittent phase of therapy, and increasing the dose of P from 10 to 15 and 20 mg/kg.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The drug dosages (in mg/kg) were as follows: INH (25 daily or 75 weekly), RPT (15), PZA (150), EMB (100), MXF (100), ETH (50), and PA-824 (100), as previously published (24,26,37). For RPT, 15 mg/kg in mice is equipotent to 15 mg/kg (900 mg) in humans (38).…”
Section: Drug Treatmentmentioning
confidence: 99%